1.5 Tesla Magnetic Resonance Imaging Features of Canine Intracranial Intra-axial Hematomas - Whitlock, James; Holdsworth, Andrew; Morales, Carles; Garosi, Laurent; Carrera, Inés (Frontiers in Veterinary Science, 2021)
The differentiation of solitary intra-axial hematomas from hemorrhagic neoplasms based on their magnetic resonance imaging (MRI) features is challenging. The treatment and prognosis for these two disease entities are vastly different and the distinction between them is often based on MRI findings alone. The aim of this study was to describe the 1.5 tesla MRI features of canine intra-axial hematomas and correlate these findings with the evolution of hemorrhages described in human brains. Retrospective evaluation of patient details, clinical signs, and MRI ﬁndings of dogs with intra-axial hematomas that were histopathologically confirmed or determined via repeat MRI study and/or resolution of neurological signs. 10 dogs met the inclusion criteria. All 10 hematoma lesions were determined to be 2-7 days in age. On MRI, all 10 hemorrhagic lesions were comprised of two distinct regions; a relatively thin T1-weighted (T1W), T2-weighted (T2W) and gradient echo (GRE) hypointense (9/10) peripheral border region and a large central region that was heterogenous but predominantly T1W, T2W and GRE hyperintense (8/10). The peripheral border region was complete in its integrity in all 10 cases on T2W and GRE sequences. Contrast enhancement was present in (6/10) hematoma lesions and was always peripheral in nature with no evidence of central enhancement associated with any of the lesions. An intra-axial hematoma should be suspected in solitary hemorrhagic space-occupying lesions that have a complete hypointense peripheral rim, elicit a peripheral contrast enhancement pattern, and display the expected temporal pattern of hematoma evolution.